2006
DOI: 10.1042/bj20051682
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type and mutant ferroportins do not form oligomers in transfected cells

Abstract: Ferroportin [FPN; Slc40a1 (solute carrier family 40, member 1)] is a transmembrane iron export protein expressed in macrophages and duodenal enterocytes. Heterozygous mutations in the FPN gene result in an autosomal dominant form of iron overload disorder, type-4 haemochromatosis. FPN mutants either have a normal iron export activity but have lost their ability to bind hepcidin, or are defective in their iron export function. The mutant protein has been suggested to act as a dominant negative over the wt (wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
41
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 38 publications
7
41
1
Order By: Relevance
“…Presumably FPN1 dimers persist in the second dimension because of insufficient equilibration of reducing agent and SDS during preparation of the first-dimension gels for the second-dimension electrophoresis. The apparent molecular mass of ϳ70 kDa for the FPN1 detected in the more slowly migrating complex also confirms that FPN1 can exist as monomers (15). Although the functional activity of the FPN1-Heph complexes cannot be determined from these studies, the presence of a dimeric form of FPN1 offers a possible explanation as to how heterozygotes for FPN1 mutations can result in iron overload (8,23).…”
mentioning
confidence: 83%
“…Presumably FPN1 dimers persist in the second dimension because of insufficient equilibration of reducing agent and SDS during preparation of the first-dimension gels for the second-dimension electrophoresis. The apparent molecular mass of ϳ70 kDa for the FPN1 detected in the more slowly migrating complex also confirms that FPN1 can exist as monomers (15). Although the functional activity of the FPN1-Heph complexes cannot be determined from these studies, the presence of a dimeric form of FPN1 offers a possible explanation as to how heterozygotes for FPN1 mutations can result in iron overload (8,23).…”
mentioning
confidence: 83%
“…The most common phenotype characterized by iron loading of macrophages and normal transferrin saturation results from mutations causing mislocalization of Fpn (eg V162del) or the loss of iron export function (eg, N174I). [7][8][9][10]22 The less common phenotype with parenchymal iron loading similar to classical hemochromatosis results from mutations that cause a gain of function, because they interfere with hepcidin-mediated internalization and degradation of Fpn (N144D/ T/H, C326S/Y, Y64N). 8,[11][12][13][14][15][16][17] Some mutations (eg, A77D) appear to cause a mixed phenotype, with both parenchymal and macrophage iron deposition, and normal to high transferrin saturation.…”
Section: Discussionmentioning
confidence: 99%
“…The loss-of-function mutations cause decreased cellular iron export because the mutant protein is retained inside the cell or has impaired iron-exporting function. [7][8][9][10] As a result, iron accumulates in macrophages, leading to very high ferritin levels, but the patients have normal-to-low transferrin saturation, and a tendency to develop anemia particularly when phlebotomized. 6 It is not yet clear whether this condition impacts health or requires treatment.…”
mentioning
confidence: 99%
“…It has been suggested that mutations in Fpn might result in cellular iron overload due to haploinsufficiency 10,12 ; however, mice that are heterozygous for a targeted gene deletion of Fpn do not show evidence of iron-overload disease. 14 To further explore the possibility that haploinsufficiency could explain decreased iron export, we used RNAi to silence mouse Fpn in macrophages.…”
Section: Mutant Fpn Ffe Acts As a Dominant Negative In Macrophages Ismentioning
confidence: 99%
“…[9][10][11] The mechanism by which the disease mutations exert a dominant effect is unclear. Some groups that study the disease suggest that it results from haploinsufficiency, 10,12 whereas others suggest that the disorder results from a dominantnegative effect of the mutant allele. 9,13 Importantly, all human mutations are missense mutations and mice that are heterozygous for a targeted deletion of Fpn do not show the disease.…”
Section: Introductionmentioning
confidence: 99%